Experiential Learning through Artwork Direct Visits in English Classroom for Art Students: An Investigation - Marga Sukma, Denty (STKIP AGAMA HINDU SINGARAJA, 2025)
AbstractEmpirical evidence on the integration of experiential learning into English Language Teaching (ELT), particularly within art-based higher education, remains underexplored despite its potential to align language development with students’ disciplinary practice. Thus, this study aims to investigate how undergraduate students majoring in Art Conservation enrolled in a state university specializing in the arts in Yogyakarta, Indonesia, engaged with English language learning through experiential learning (EL) activities, particularly direct visits to public artworks. Drawing on a qualitative case study approach, data were collected from in-depth interviews and student reflective essays, with participants recruited to this current study being purposively selected. Through thematic analysis, the findings reveal how the direct visits to the artworks can enhance the students’ skills useful for their learning in the English classroom and their future professional endeavors. It indicates that direct engagement with artworks in real-life settings significantly enhances students’ learning experiences. These visits supported the development of key academic and professional skills, such as critical thinking, communication, and information retention, by encouraging active observation, personal interpretation, and reflective analysis. The study concludes that experiential learning can provide meaningful opportunities for students to internalize abstract concepts through real-world engagement. Incorporating such activities into language education may foster more profound learning, enhance writing quality, and promote holistic development. These findings underscore the value of integrating experiential methods within higher education settings, particularly art-based majors.